Legal implications of conversion to the religion of Islam in Malaysia : an analytical appraisal of law and judical interpretations - Narizan binti Abdul Rahman (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2011)
Recently, issues pertaining to conversion to the religion of Islam have invited substantial public attention. Notably, the issue has been raised globally in various societies for centuries. In the Malaysian context it has been debated for a long time as depicted by scholarly writings in available literature. However, it gained exceptional momentum recently as is evident by reportings in the mass media. To date, legal disputes relating to the conversion have received wide coverage in the daily newspapers and it commands substantial debates among the legal fraternity on a scale and volume which are not seen before. This study is undertaken to analyse certain aspects of legal implications of the conversion to the religion of Islam within Islamic and Civil law perspectives. This study is comparative in nature and it covers legal implications of the conversion in both Islamic and Civil laws pertaining to matters of personal law, including marriage and matrimonial obligation, property rights and criminal law. The study primarily undertakes to analyse the legal position adopted in all reported cases pertaining to the conversion. Content analysis technique has been used throughout the analysis. In addition, field study has been carried out in both Civil and Shariah courts in four states in Malaysia to gather data on relevant unreported cases in these courts. Necessary interviews with courts officials also had been conducted in order to gather informations which are unavailable in courts files. Compared to other states, these four states comprising of Federal Territory, Selangor, Sabah and Sarawak were selected as they represent significant segment of non-Muslim population in Malaysia and more cases pertaining to the conversion are expected to materialise . However, due to financial and time constraints, the study has been undertaken in the states capitals only. The purpose of the study is to identify and analyse any differences bound to occur between the reported and unreported cases. Apart from courts, significant study also has been carried out in relevant government departments, particularly, States Islamic Religious Affairs Departments which are entrusted directly with administration and management of conversion to the religion of Islam. The study has been able to provide certain interesting findings. The study has shown that legal conflicts in both civil law and Islamic law pertaining to the implications of conversion to the religion of Islam are bound to occur in all aspects of personal law under investigation. However, certain aspects of implications, for instance dissolution of marriage and conversion of minor children to the religion of Islam are frequently invoked in courts compared to other aspects. Nevertheless, certain legal avenues which will reduce the conflict have been identified. It is further found that governing legislations on the conversion, lack uniformity and standardisation in terms of substance and procedures. Certain states have complete rules and regulations pertaining to the conversion but other states have not even codified any rules and regulations. The gap is significant. Finally this study has been able to provide some suggestions and recommendations with regard to approaches to solutions to be adopted by law and policy makers.